Letter Gloves Media with Storytelling : Effect on Letter Recognition in Children in Kindergarten Pekanbaru - Widiawati Widiawati; Rakimahwati Rakimahwati (AL-ISHLAH: Jurnal Pendidikan, 2023)
Language is a verbal communication medium that humans use to interact with each other. Basically, early childhood language development includes four developments, namely listening, speaking, reading, writing, and recognizing letters by reading. The purpose of this study was to find out how much influence the letter glove media has on the ability to recognize letters in children aged 4-5 years in Kindergarten. This type of research is experimental research using a one group design with pretest and posttest through observation sheets. From the results of the research and from the discussion, it was concluded that the ability to recognize children's letters before being given treatment through the media of letter gloves with the storytelling method was considered low, this was seen from the individual categories of children, namely 20 children who were categorized as medium 25%, low 75%, and high 0%. After going through the letter glove media with the storytelling method, the child's ability to imprint letters increased, namely 60% Medium was categorized as high, 40% was categorized as medium and no children were in the low category.